Geofluids : developments in microthermometry, spectroscopy, thermodynamics, and stable isotopes /: developments in microthermometry, spectroscopy, thermodynamics, and stable isotopes. (2015) - Hurai, Vratislav; Huraiová, Monika; Slobodník, Marek; Thomas, Rainer
No abstract available